Short Communication: The study of suweg (Amorphophallus paeoniifolius) and other undergrowth species in teak plantation forest of Temengeng, Blora, Indonesia - SYAMSUL HIDAYAT (Biodiversitas Journal of Biological Diversity, 2019)
Hidayat S. 2019. The study of suweg (Amorphophallus paeoniifolius) and other undergrowth species in teak plantation forest of Temengeng, Blora, Indonesia. Biodiversitas 20: 37-42. Suweg (Amorphophallus paeoniifolius (Dennst.) Nicolson) is one of the potential sources of food plants that are often found growing wild in farmers' gardens or fields. In the teak plantation forest of Cepu, precisely in Temengeng village, there are many suwegs growing among the old and big teak trees. To find out the potential and range of habitat where suweg grows, especially in teak plantation forest, ten observation plots were made using purposive sampling method, each measuring 10 x 10 m2. Overall, 17 adults and 30 young individuals of suweg were found. In addition to teak, 43 wild plant species were identified alongside suweg, from various habits, namely herb, liana, shrub, epiphyte, and tree. Herbs were the most common plants growing around suweg, especially from the families of Fabaceae, Compositae, and Zingiberaceae. The species that were almost always found together in the suweg plots were Tetrastigma lanceolarium (Roxb.) Planch. and Thespesia lampas (Cav.) Dalzell, but in quantity, Costus spiralis (Jacq.) Roscoe was more abundant than the other two species, although it was only found in four sampling plots. The results of this study also showed that there was no association between suweg and certain plants; this was supported by the low similarity index among plots.